(untitled) (Research, Society and Development, 2022)
The main objective of this research is to analyze in a preliminary way the Cariri Ocidental region of Paraiba, to detect which would be the possible types of cultures that may have greater viability of agrarian development in the region studied, based on an area located in the semi-arid region of Paraiba. As a methodology applied in this research, the GIS mapping program was used, A geographic information system, also known as GIS, is a system of hardware, software, spatial information, computational procedures and human resources that allows and facilitates the analysis, management or representation of geographic information. The main results obtained went beyond being able to measure which cultures are most suitable through analysis of thematic maps with characteristics capable of providing information with some anticipation and reliability. Having a good systematic evaluation of the studied environment with the purpose of applying in these studied soils correction systems or cultures conniving to their nutrients found through the research. It is concluded that the use of GIS provides a more detailed and careful conception of which type of culture can be applied to a study area, with the purpose of better agricultural quality and better environmental performance.